Bangladeshi Students Perceptions of Flipped Classroom: A Case Study - Md. Naeem Aziz (Journal of Learning and Educational Policy, 2022)
This paper attempts to bring out the pros and cons of implementation of flipped classroom in Bangladesh. It is a case study conducted on three hundred fourteen students from different places and educational levels of Bangladesh who gave their perception and of information about the flipped classroom. The collected data had been gathered through the usage of each quantitative and qualitative technique The effects showed that maximum students felt secure with the usage of the flipped study room, and maximum students could recommend flipped getting to know exclusive guides and other students concerning the feedback from the students. The coronavirus shows the world the importance of the flipped classroom. Maximum students support the flipped classroom in a situation like covid19 but they don’t want flipped class in normal situations. They also don’t want the flipped classroom in their daily life but they will welcome flipped classes in a situation like covid19. The flipped classroom is great for those who need time to study cause flipped classroom system gives a lot of time for studies. But normal physical class is more effective to understand for everybody.